2021
DOI: 10.1002/pbc.29517
|View full text |Cite
|
Sign up to set email alerts
|

Family bonding as a result of the family talk intervention in pediatric oncology: Siblings’ experiences

Abstract: Background Childhood cancer affects the whole family. Illness‐related stressors increase the risk for poor family communication, affecting the family's well‐being. Siblings describe worry and poor illness‐related information. As there are few evaluated family interventions in pediatric oncology, this study aimed to pilot‐test a family‐centered intervention, the family talk intervention (FTI), in pediatric oncology. This paper examined the feasibility in terms of acceptability from the siblings’ perspectives. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Although most siblings in the study found it sufficient to talk with their parents, parents may need help understanding that siblings need to talk and could benefit from improved knowledge of how to do this. Some interventions may be helpful to improve parent—sibling communication, such as the family talk intervention (Ivéus et al, 2022 ; Lövgren et al, 2022 ) or SIBS (Haukeland et al, 2020 ). Our study shows that it may be difficult for siblings to talk with their parents when they are at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Although most siblings in the study found it sufficient to talk with their parents, parents may need help understanding that siblings need to talk and could benefit from improved knowledge of how to do this. Some interventions may be helpful to improve parent—sibling communication, such as the family talk intervention (Ivéus et al, 2022 ; Lövgren et al, 2022 ) or SIBS (Haukeland et al, 2020 ). Our study shows that it may be difficult for siblings to talk with their parents when they are at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches used by the reviewed articles to empower parents were providing information and support for parents, and facilitating discussion and experience sharing with their own family members and other parents of children with cancer. It is also achieved through helping parents to give attention for their family relationship, care for the emotional and physical needs of their child with cancer, planning on how to communicate with the child, and breaking the silence together as a family and continuing the family dialogue (34,36,40,44). Similarly a systematic review by Park et al (50) identi ed empowerment as a key component of FCC intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Families who received FCC has reported improved interaction with staff and each other, communicate better and felt understood by HCP (39,40,43). Parents who received person centered information has reported the opportunity they got to ask questions about their child's prognosis was the reason for being satis ed with care received (42).…”
Section: Family Related Outcomes Of Fcc Interventionmentioning
confidence: 99%
“…In conjunction with the end of the FTI, the parents were invited to be interviewed by a researcher (the children's experiences are reported elsewhere 19,20 ). The primary focus of the interviews was the parents' experiences of taking part in the FTI, and parents were initially asked to freely describe their overall experience of the FTI.…”
Section: Data Collectionmentioning
confidence: 99%